Measuring The Impact Of Digital Advisory On Customer Portfolio: A Quasi-Experimental Approach Using Propensity Score Matching - Satya, Yudha; Sudiarno, Adithya (Syntax Corporation, 2025)
Digital financial advisory services are increasingly recognized for their potential to promote financial inclusion and support portfolio development, especially among underserved retail customers. This study investigates the causal impact of digital advisory interventions on customer financial performance, with a focus on asset growth and financial product diversification. Employing a quasi-experimental approach using Propensity Score Matching (PSM), the research draws upon a cross-sectional dataset of 5,200 customers in Indonesia, evenly divided into treatment and control groups. Initial selection bias was assessed using Chi-square and Mann–Whitney U tests, followed by logistic regression to estimate propensity scores based on demographic, financial, and channel covariates. Nearest neighbor matching without replacement was applied, and subsequent diagnostics confirmed improved balance of covariates. The Average Treatment Effect on the Treated (ATT) indicates that digital advisory recipients experienced significant portfolio growth, with higher asset growth (IDR 11.4 million) and an increased acquisition of financial products (+0.34) compared to their matched counterparts. These findings provide robust empirical support for the role of digital advisory services in fostering financial engagement and inclusive economic growth.